An Investigation of Inhibition Effects of Honey, Pollen, Propolis and Royal Jelly Extracts on Thioredoxin Reductase Enzyme Activity - Gamze Akbulut; Ebru Akkemik (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
The thioredoxin reductaseenzyme is an enzyme that prevents the mechanism of apoptosis from working andthus triggers the formation of cancer. Therefore, the inhibition of thethioredoxin reductase enzyme is thought to prevent or inhibit cancer. In thisstudy, the effects of extracts of plateau honey, pine honey, chestnut honey,mad or wild honey, pollen, propolis and royal jelly on thioredoxin reductaseenzyme activity were investigated. Enzyme activities were measured at constantsubstrate and different inhibitor concentrations to calculate IC50values. Over five different inhibitor concentrations were used for measuringthe inhibition constant. Total antioxidant activity were investigated in orderto compare the extracts used in the inhibition study. The strongest inhibitoryeffect was seen in the pollen methanol extract (IC50 = 2.44μg /mL)